The clinical characteristics and risk factors for necrotizing soft tissue infection in children - Jing Liu; Jigang Chen; Yanni Wang; Hongyan Qi; Jing Yu (Pediatric Investigation, 2024)
ABSTRACT Importance Necrotizing soft tissue infection (NSTI) is a serious infectious disease. However, the early clinical manifestations and indicators of NSTI in children are still unclear. Objective The purpose of this study was to analyze the clinical characteristics and risk factors of NSTI in pediatric patients. Methods A total of 127 children with skin and soft tissue infection (SSTI) were treated at our hospital and divided into two groups: the NSTI group and the non‐NSTI group, based on their discharge diagnosis from January 2011 to December 2022. Then, we collected and analyzed the clinical characteristics and risk factors of all patients, including sex and age, disease inducement, admission temperature, local skin manifestations, infection site, the presence of sepsis, bacterial culture, and laboratory indicators. Results In our study, there was a statistical difference in the age distribution and disease inducement between NSTI and non‐NSTI groups. The occurrence of local skin manifestations (blisters/bullae and ecchymosis) and the presence of sepsis significantly increased in the NSTI group compared to the non‐NSTI group. Additionally, only the platelet count on laboratory tests was statistically different between the NSTI and non‐NSTI groups. Finally, the logistic regression analysis suggested that local skin manifestations such as blisters/bullae, and ecchymosis, as well as the presence of sepsis, were identified as risk factors for NSTI. Interpretation Children with SSTI and skin manifestations such as blisters/bullae, ecchymosis, and the presence of sepsis are at a higher risk of developing NSTI. These symptoms serve as useful indicators for early detection of NSTI.